2009
DOI: 10.1016/j.immuni.2009.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Lamina Propria Dendritic Cell Network

Abstract: CX3CR1+ and CD103+ dendritic cells (DCs) in intestinal lamina propria (LP) play a key role in mucosal immunity. However, the origin and the developmental pathways that regulate their differentiation in the LP remain unclear. Our results reveal that monocytes give rise exclusively to CX3CR1+CD103− LP DCs under the control of M-CSFR and Flt3 ligands. In contrast, common DC progenitors (CDP) and pre-DCs, which give rise to lymphoid organ DCs but not to monocytes, differentiate exclusively into CD103+CX3CR1− LP DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

52
947
2
16

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 759 publications
(1,022 citation statements)
references
References 48 publications
52
947
2
16
Order By: Relevance
“…The mutually exclusive expression of monocyte markers and Flt3 by CD103 À and CD103 1 DC, respectively, strongly suggests that the two DC subsets develop from different progenitors. Our data are in agreement with two recent studies showing that at the steadystate, LP CD103 1 CX 3 CR1 À/low DC arise from common DC progenitors and pre-DC without a monocytic intermediate through a Flt3 ligand-mediated pathway whereas CD103 À CX 3 CR1 1 DC derive from Ly6C hi monocytes [10,21]. In addition, our results indicate that the developmental distinction between CD103 1 and CD103 À DC in MLN is retained during intestinal inflammation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The mutually exclusive expression of monocyte markers and Flt3 by CD103 À and CD103 1 DC, respectively, strongly suggests that the two DC subsets develop from different progenitors. Our data are in agreement with two recent studies showing that at the steadystate, LP CD103 1 CX 3 CR1 À/low DC arise from common DC progenitors and pre-DC without a monocytic intermediate through a Flt3 ligand-mediated pathway whereas CD103 À CX 3 CR1 1 DC derive from Ly6C hi monocytes [10,21]. In addition, our results indicate that the developmental distinction between CD103 1 and CD103 À DC in MLN is retained during intestinal inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…CD103 1 DC represent a sentinel DC population in the small intestine (SI) and can migrate to the MLN to initiate adaptive immune responses [10]. Under homeostatic conditions, CD103 1 DC in MLN promote the development of Foxp3 1 Treg.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis of CD103 expression on T cells concludes that GM-CSF does not grossly affect the CD103 expression on T cells. Apart from T cells and resident CD8 1 DCs, certain mucosal DCs [31,32] and dermal DCs also express CD103 [33]. GM-CSF deficiency did not affect the numbers of resident CD8 1 DCs, but led to a severe reduction in the numbers of dermal CD103 1 DCs [33].…”
Section: Discussionmentioning
confidence: 97%
“…Similar observations regarding the capacity of intestinal IL-6 to promote immune responses in Crohn's disease patients have been recently described [29]. Future studies should identify specific mechanisms and signaling pathways through which IL-6-mediated effects are established on DCs.Given the dual capacity of DCs to control both immunogenic and tolerogenic immune responses, recent mouse studies have suggested that two different tolerogenic (CD103 + ) and proinflammatory (CX3CR1 + ) nonoverlapping DCs subpopulations coexist in the gut [30][31][32]. These findings suggest that DCs responsible for regulatory and inflammatory responses might be of distinct origin, phenotype and function in resting and inflammatory conditions.…”
mentioning
confidence: 99%